Upscaling of a diffusion problem with interfacial flux jump leading to a modified Barenblatt model. Issue 2 (18th October 2018) - Bunoiu, Renata; Timofte, Claudia
Abstract: In this paper, we study the homogenization of a diffusion problem in a highly heterogeneous composite medium formed by two constituents separated by an imperfect interface, where both the temperature and the flux exhibit jumps. The presence of the flux jump leads to a modified stationary Barenblatt model. Besides, we discuss two different geometrical settings, providing a mathematical justification for a physical phenomenon which is explained by the connectivity properties of the constituents. Abstract : In this paper, we study the homogenization of a diffusion problem in a highly heterogeneous composite medium formed by two constituents separated by an imperfect interface, where both the temperature and the flux exhibit jumps. The presence of the flux jump leads to a modified stationary Barenblatt model. Besides, we discuss two different geometrical settings, providing a mathematical justification for a physical phenomenon which is explained by the connectivity properties of the constituents.